Diagnostic accuracy of magnification endoscopy with acetic acid enhancement and narrow-band imaging in gastric mucosal neoplasms - Shibagaki, Kotaro; Amano, Yuji; Ishimura, Norihisa; Taniguchi, Hideaki; Fujita, Hiraku; Adachi, Seiji; Kakehi, Eichi; Fujita, Ryosuke; Kobayashi, Keita; Kinoshita, Yoshikazu (Endoscopy, 2016)
Background and study aims: Magnification endoscopy with narrow-band imaging (NBIME) and NBIME with acetic acid enhancement (A-NBIME) visualize the capillary and microstructure patterns of the gastric mucosal surface, respectively. This study aimed to compare the diagnostic accuracy and interobserver agreement for white-light endoscopy (WLE), NBIME, and A-NBIME in the different histologic types of gastric mucosal neoplasm.Patients and methods: Consecutive gastric neoplasms (n = 220; 49 adenomas, 144 differentiated adenocarcinomas, and 27 undifferentiated adenocarcinomas) were photographed with WLE, NBIME, and A-NBIME. Macroscopic patterns using WLE, capillary patterns using NBIME, and microstructure patterns using A-NBIME were respectively classified into type M1/M2/M3, type C1/C2/C3/C4, and type S1/S2/S3, as the indicators of adenoma, differentiated adenocarcinoma, and undifferentiated adenocarcinoma (Type C4, unevaluable because of capillary invisibility), according to the previously reported classifications. Endoscopic images were independently reviewed by three experts and three non-experts. Diagnostic accuracy and interobserver diagnostic agreement were compared among the modalities.Results: Kappa values (95 % confidence interval [CI]) for WLE, NBIME, and A-NBIME diagnosis were 0.36 (0.33 – 0.39), 0.58 (0.54 – 0.61), and 0.62 (0.55 – 0.68) for experts and 0.31 (0.29 – 0.33), 0.36 (0.34 – 0.38), and 0.52 (0.48 – 0.56) for non-experts, showing good reproducibility of A-NBIME diagnosis regardless of proficiency. All experts and non-experts diagnosed the histologic types statistically more accurately with A-NBIME than with WLE and NBIME (P < 0.05). Overall the “experts-agreed” diagnostic accuracy (95 %CI) was 75.5 % (70.0 – 81.0) for WLE vs. 74.1 % (67.6 – 80.6) for NBIME vs. 90.5 % (86.7 – 94.1) for A-NBIME (P < 0.05). WLE and NBIME were insufficient to predict the diagnosis of adenomas and undifferentiated adenocarcinomas.Conclusion: A-NBIME showed statistically significantly higher diagnostic accuracy for gastric mucosal neoplasms, with good reproducibility, compared with WLE and NBIME, which provided similar lower accuracy.